2017
DOI: 10.1101/134072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The N-terminal domain of ALS-linked TDP-43 assembles without misfolding

Abstract: TDP-43 forms inclusions in several neurodegenerative diseases, and both its N- and C-terminal domains are implicated in this process. We show that the folded TDP-43 N-terminal domain oligomerizes under physiological conditions and propose that, in full-length TDP-43, association between folded N-terminal domains enhances the propensity of the intrinsically unfolded C-terminal domains to drive pathological aggregation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Several groups have reported that TDP‐43 NTD mediates assembly into dimers or other higher‐order structures (Shiina et al , ; Chang et al , ; Wang et al , ), though the details of the assembly have only recently begun to be visualized with atomistic resolution (Afroz et al , ; Jiang et al , ; Mompean et al , ; Tsoi et al , ). Recombinant TDP‐43 NTD (in our case: residues 1–80, with only three additional N‐terminal residues, GHM, resulting from the cloning strategy and cleavage with TEV protease) is highly soluble when expressed and purified from bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have reported that TDP‐43 NTD mediates assembly into dimers or other higher‐order structures (Shiina et al , ; Chang et al , ; Wang et al , ), though the details of the assembly have only recently begun to be visualized with atomistic resolution (Afroz et al , ; Jiang et al , ; Mompean et al , ; Tsoi et al , ). Recombinant TDP‐43 NTD (in our case: residues 1–80, with only three additional N‐terminal residues, GHM, resulting from the cloning strategy and cleavage with TEV protease) is highly soluble when expressed and purified from bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…We chose to use a construct that encompasses both the N-terminus and the RRM domains taking the start from our previous work on the RRM domains [23]. We decided to include also the N-terminus for various reasons: while the prion-like potential of the C-terminus has been associated to the pathological aggregation of TDP-43 [42], growing evidence indicates the importance of the N-terminally driven oligomerization for physiological self-assembly into stress granules [43], [44]. The N-terminal domain is also involved in the native functional dimerization of the protein, which is considered to increase the risk of aberrant self-interactions and aggregation of the protein [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…In the various structural studies so far reported, the isolated NTD domain was found to adopt either a dimeric (34,39,55,56) or oligomeric (18,19,57,58) state. Moreover, it was suggested that the native (nonmisfolded) full-length protein might adopt a complex oligomeric state because of the ability of the CTD to increase the oligomerization state of the protein (18,19).…”
Section: Refolded Pelb-tdp-43-his Is a Dimermentioning
confidence: 99%